Avaliação da permeabilidade da papaína em formulações orais para tratamento de patologias intestinais utilizando tripla co-cultura de células Caco-2, HT29-MTX e Raji como modelo in vitro - Corazza, Fulvio Gabriel [UNIFESP] (2018)
Papain is a phytoenzyme used in therapy for the treatment of wounds due to its proteolytic debridant activity capable of stimulating healing. Besides that, this enzyme can also be used as pharmaceutical actives permeation enhancer. The objective of the present study was to evaluate in vitro the cytotoxicity, phototoxicity, genotoxicity and capacity of samples containing free and complex papain with β-cyclodextrin and 2-hydroxypropyl-β-cyclodextrin and minitablets containing free papain in promoting the maintenance of furosemide through the Caco-2 cell monolayer and the triple co-culture of Caco-2, HT29-MTX and Raji cells. IC50 (μM) of papain on BALB/c 3T3 cells, CHO-K1, Caco-2, HuTu 80, HT-29, HT29-MTX, Raji. Hep G2 and human fibroblasts was 3.8; 4.9; 1.4; 0.4; 4,5; 2,3; 2.6 and 1.6, respectively. The IC50 (μM) of papain complexed with β-cyclodextrin on the same cell lines was 3.7; 3.5; 1.4; 2.8; 5.3; 1.9; 3.0; 1.8, respectively. The IC50 (μM) of papain complexed with 2-hydroxypropyl-β-cyclodextrin on the same cell lines was 4, 2; 2.5; 1,3; 3.3; 5.1; 1.8; 2.9; 1.5, respectively. Papain formulations did not show cytotoxicity on Raji cells and were unable to promote LDH release. In the phototoxicity evaluation, papain and its cyclodextrin complex were considered nonphototoxic at concentrations lower than 0.67 μM. In the genotoxicity assessment, the samples also did not promote genotoxicity on CHO-K1 and Hep G2 cells at the concentrations evaluated. Using the Caco-2 cell monolayer model, the Papp of furosemide was 2.8 x 10-6 cm.s1 and 7.0 x 10-6 cm.s-1 in the presence of the formulations of papain complexed with cyclodextrins. Meproprolol showed Papp of 24 x 10-6 cm.s-1 . rhodamine 123 (ROD123) efflux ratio was 0.2 and the Lucifer Yellow (LY) Papp was 4.3 x 10-7 cm.s-1 , indicating the presence of P-gp and paracellular integrity. Using the triple co-culture monolayer model, Papp of furosemide was 0.6 x 10-6 cm.s-1 and on average 0.8 x 10-6 cm.s-1 in the presence of formulations of papain complexed with cyclodextrins. Meproprolol presented Papp of 7.1 x 10-6 cm.s-1 . The ROD123 efflux ratio was 0.1 and the LY Papp was 3.8 x 10-7 cm.s-1 , indicating the presence of P-gp and maintaining the paracellular integrity of the cell monolayer. The results presented suggest that papain formulations complexed with cyclodextrins could be employed not only as therapeutic agents in the treatment of colonic pathologies but also as therapeutic adjuvants foccus in promoting permeation of drugs which have low oral permeability.